1989
DOI: 10.1159/000125116
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Thyrotropin-Releasing Hormone on in vitro Release of in vivo or in vitro Newly Synthesized and Mature Prolactin by Lactating Rat Adenohypophyses

Abstract: We studied the basal and thyrotropin-releasing hormone (TRH)-stimulated in vitro release of newly synthesized and mature prolactin (PRL) by lactating rat pituitary fragments. Newly synthesized PRL was defined as that resulting from either in vivo pulse labelling with [3H]-leucine (injected i.v. 10 min before removing the pituitary glands for in vitro incubation); or in vitro labelled by a 5-min preincubation period of adenohypophyseal fragments. Mature PRL was defined as that labelled in vivo 8 h be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It shows that stimulation of PRL secretion does not involve mobilization of newly synthesized PRL. The rationale for analyzing the release of [ 3 H]-prelabeled PRL is that in estrogen-treated females [10, 33] or in lactating rats [11, 12], newly synthesized and mature [ 3 H] PRL show different patterns of secretion, mainly through the regulated secretory pathway [10], which may be influenced by hypothalamic secretagogues [13, 14]. Following PRL labeling with [ 3 H] leucine, we found that upon stimulation with CM, PRL release displays essentially the same pattern, regardless of the length of time (between 30 min and 24 h) that elapsed between [ 3 H] PRL labeling and incubation with CM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It shows that stimulation of PRL secretion does not involve mobilization of newly synthesized PRL. The rationale for analyzing the release of [ 3 H]-prelabeled PRL is that in estrogen-treated females [10, 33] or in lactating rats [11, 12], newly synthesized and mature [ 3 H] PRL show different patterns of secretion, mainly through the regulated secretory pathway [10], which may be influenced by hypothalamic secretagogues [13, 14]. Following PRL labeling with [ 3 H] leucine, we found that upon stimulation with CM, PRL release displays essentially the same pattern, regardless of the length of time (between 30 min and 24 h) that elapsed between [ 3 H] PRL labeling and incubation with CM.…”
Section: Discussionmentioning
confidence: 99%
“…Animals were euthanized by decapitation after light ether anesthesia. It has been shown that this procedure does not alter pituitary PRL content [11,12,13,14]. …”
Section: Methodsmentioning
confidence: 99%
“…The existence of multiple secretory pathways within endocrine cells has been receiving increasing attention (1)(2)(3)(4)(5). In some cases there is evidence for independently regulated pathways, for example in prolactin-producing cells (6) and parathyroid hormone-producing cells (7,8).…”
mentioning
confidence: 99%